The Epstein/Maxwell Blackmail Operation (Political Film Blog, 2021)
Jan 2020: “Epstein was blackmailing prominent politicians on behalf of Israeli intelligence.” Jeffrey Epstein was blackmailing politicians for Israel’s Mossad